Investigation of the Dependence Structure Between Imports and Manufacturing Production Index of Thailand using Copula-Based GARCH Model : Chakorn Praprom, Songsak Sriboonchitta - Team, Support (Thai Journal of Mathematics, 2014)
This paper aims at investigating the dependence structure betweenthe imports and the manufacturing production index of Thailand using a copula-GARCH approach. We applied skewed student-t distribution to estimate all of themarginal distributions with ARMA(1,12)-GARCH(1,1), ARMA(1,2)-GARCH(1,1)to t the manufacturing production index (MPI) and the imports of Thailand.The results of this paper suggest that the student-t copula is the most appropriatemethod to best t the tail dependences in both static and time-varying copulasbecause the AIC and the BIC of this method are the lowest when compared withthe candidates among the other types of copula.